Lactobacillus rhamnosus GG (LGG®) probiotic: what do we know about its efficiency and safety? - S. G. Gribakin; A. G. Timofeeva; O. A. Bokovskaya (Лечащий Врач, 2021)
Current data on the role of probiotic strain Lactobacillus rhamnosus LGG® in pediatric practice are presented. LGG® strain is widely used both as a component of infant formulas and of medical preparations. Lactobacillus LGG® has a high degree of resistance to gastric acid and to bile salts, due to pili, the adhesion to intestinal epithelial cells is realized. LGG® is characterized by an active persistance of colonization of human colonic mucosa. Besides the inhibition of pathogens they participate in intestinal microbiota modulation, support reduction of risk of allergic diseases and provide formation of immunological tolerance.